1970
DOI: 10.3126/njog.v2i2.1456
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and acceptability of medical abortion with mifepristone and misoprostol in Nepalese women

Abstract: Unsafe abortion is a major health issue. Therefore safe abortion services which is effective. acceptable and techniquely easy to perform should be available. AimAim Aim Aim Aim-To confirm effectiveness, side effects, safety and patient satisfaction with medical termination of early pregnancy.MethodsMethods-MethodsMethods-Methods-It was a prospective study 150 women who were less than 63 days pregnant and consented for medical termination of pregnancy were given! 200mg 0 Mefepristone orally and 48 hrs later 800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…4 Pattern of side effects: Vaginal bleeding and uterine cramping (usually heavier than with menstruation) are expected. 10 In our study, women undergoing MTP experienced minimum 4 days and maximum 9 days of vaginal bleeding. None of the women reported heavy bleeding (Heavy bleeding: Two soaked maxipads in 1 hour for 2 consecutive hours 12 ), and none required a transfusion.…”
Section: Success Rate Of the Combination (Mifepristone And Misoprostomentioning
confidence: 68%
See 1 more Smart Citation
“…4 Pattern of side effects: Vaginal bleeding and uterine cramping (usually heavier than with menstruation) are expected. 10 In our study, women undergoing MTP experienced minimum 4 days and maximum 9 days of vaginal bleeding. None of the women reported heavy bleeding (Heavy bleeding: Two soaked maxipads in 1 hour for 2 consecutive hours 12 ), and none required a transfusion.…”
Section: Success Rate Of the Combination (Mifepristone And Misoprostomentioning
confidence: 68%
“…In her prospective study, Misoprostol was used vaginally and the success rate was 92.6%. 10 Kathleen et al, in 2011 performed a similar research with misoprstol administered vaginally, and the success rate was 80 %. 11 Recently, sublingual administration of Misoprostol has been studied for medical abortion and cervical priming.…”
Section: Success Rate Of the Combination (Mifepristone And Misoprostomentioning
confidence: 98%
“…In her prospective study misoprostol was used vaginally and the success rate was 92.6%. 11 Kathleen et al in 2011 performed a similar research with Misoprostol administered vaginally and the success rate was 80%.…”
Section: Discussionmentioning
confidence: 96%
“…9,10 This was because systemic bioavailability of misoprostol was 4 times higher through vaginal route when compared with oral route and peak level was attained more slowly but was sustained for longer periods. 11 The success rate of taking a 48 hour interval between the medications ranges from 92-97%. 2,12 Crenin et al reported success rate of 24 hour regimen to be 98.1% and 96.9% in their studies carried out in 2004 and 2007.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several studies have studied the vaginal use of misoprostol. 1,5,8 Our study evaluated the efficacy, side effects and acceptability of its sublingual use.…”
Section: Discussionmentioning
confidence: 99%